Functional cleft palate surgery - Ulrich Joos; Anthony F. Markus; Robert Schuon (Journal of Oral Biology and Craniofacial Research)
Cleft lip and palate (CLP) as a dislocation malformation confronts parents with a malformation of their child that could not be more central and visible: the face. In addition to the stigmatizing appearance, however, in cases of a CLP, food intake, physiological breathing, speech and hearing are also affected.In this paper, the principles of morphofunctional surgical reconstruction of the cleft palate are presented. With the closure of the palate, and restoration of the anatomy, a situation is achieved enabling nasal respiration, normal or near normal speech without nasality, improved ventilation of the middle ear, normal oral functions with coordinated interaction of the tongue with the hard and soft palate important for the oral and pharyngeal phases of feeding. With the establishment of physiological function, in the early phases of the infant and toddler, these activities initiate essential growth stimulation, leading to normalisation of facial and cranial growth. If these functional considerations are disregarded during primary closure, lifelong impairment of one or more of the abovementioned processes often follows. In many cases, despite secondary surgery and revision, it might not be possible to correct and achieve the best possible outcomes, especially if critical stages of development and growth have been missed or there has been significant tissue loss due to resection of existing tissue while primary surgery.This paper describes functional surgical methods and reviews long term, over many decades, results of children with cleft palate.